China's tourism development, contemporary market analysis and future prospects - shen, ziwen (2008)
China's tourism industry is the achievement of the openness to the outside world and the implementation of economics reform. With years of changes in Chinese political and economic sectors, it has grown out of nothing, and experienced progress from small to large, from rapid growth to steady development, reaching toward its maturity since 1978. This paper explains the main stages of its development and indentifies the important changes before 2000. Moreover this paper shows that China's tourism makes a significant contribution in promoting regional economics growth, improving local economics structures, driving the development of related industries, increasing the employment rate and activating domestic demand in 2000s. The result of contemporary tourism development and current market analysis are given in this paper. And it also analyzes the opportunities and challenges with which China's domestic tourism is confronted, and further suggests the choices of policies and market strategies that China should undertake for its tourism development. All the findings in this paper provide the important implications in studying the social and political dimensions of tourism in China.